Mechanical Properties and Recyclability of Ionic Thermoplastic Rubber Based on Citraconated Ethylene Propylene Diene Monomer - Bae1, J.W.; Kim1, J.S.; Lee1, J.H.; Kim1, G.N.; Oh1, S.T.; Lee2, Y.H.; Kim2, H.D. (Asian Journal of Chemistry, 2013)
The mechanical properties and recyclability of novel ionomers based on citraconated ethylene propylene diene monomer (EPDM) were examined. Citraconated EPDM (CCA-g-EPDM) was synthesized using a melt grafting technique from citraconic acid (CCA)/EPDM/free radical initiator [2,5-dimethyl-2,5-di(tert-butyl peroxy) hexane: L-101]. Ionomers (IZnO(5), IZnO(10), IZnSt.(5), IZnSt.(10), IZnO(5)/ZnSt.(5)) based on citraconated EPDM were prepared by melt mixing from CCA-g-EPDM and zinc oxide and/or zinc stearate using a Haake Rheocorder. This study compared the mechanical properties of pristine EPDM, CCA-g-EPDM and pristine/recycled ionomers. The density, tensile strength, elongation at break, modulus and tear strength increased in the order, ionomers > CCA-g-EPDM > pristine EPDM, whereas the compression set was in the opposite order. The ionomer, IZnO(5)/ZnSt.(5), exhibited the highest mechanical properties and showed no significant change in the mechanical properties and compression set with successive recycling. These results suggest that the recyclable ionomers based on citraconated EPDM prepared in this study have high potential as new high performance thermoplastic elastomers.